Learn MySQL from scratch. - Safari eBooks ([Place of publication not provided] : Stone River eLearning, 2014)
"If you're new to web development, MySQL is the most popular database technology out there. This free technology is used to create the majority of database dependent websites (which most are). This course will start at the very beginning, with lessons on what MySQL is and how it works, to installing MySQL, then moving on to all the basic skills you'll need to use MySQL in the real world. You will also learn the popular new MySQLi framework. MySQLi is the next generation of MySQL, and if you know this now you will be ahead of the competition for a long time to come."--Resource description page.
Title from resource description page (viewed December 4, 2014).
Keywords: MySQL (Electronic resource); SQL (Computer program language); PHP (Computer program language); Web sites -- Design; Web site development; Electronic books